1973
DOI: 10.1111/j.1348-0421.1973.tb00942.x
|View full text |Cite
|
Sign up to set email alerts
|

Impairment and Restoration of the Delayed Type Hypersensitivity in Germ‐Free Mice

Abstract: It was reported previously [8] that germfree (GF) mice infected with virulent bovine type tubercle bacilli showed more extensive and progressive infections than conventional mice; marked differences between GF and conventional mice were observed only in later stages of the infections. The lesions in GF mice were characterized by infiltration with many histiocytic cells engorging acid fast bacilli. These facts seemed to implicate an impaired immunological response following the infection in GF mice. It has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
1
5
0
Order By: Relevance
“…Lev and Battisto (15) reported that lymphoid cells from specifically immunized guinea pigs can transfer tuberculin sensitivity to CONV recipients but not to guinea pigs that have been reared in a GF environment. Similar observations have been made in mice (32). Preliminary experiments performed in rats (Jungi and McGregor, unpublished data) indicate that labeled lymphoblasts from the thoracic duct lymph of Listeria-infected CONV donors can move in substantial numbers from the blood into Listeria-induced exudates borne by GF rats.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Lev and Battisto (15) reported that lymphoid cells from specifically immunized guinea pigs can transfer tuberculin sensitivity to CONV recipients but not to guinea pigs that have been reared in a GF environment. Similar observations have been made in mice (32). Preliminary experiments performed in rats (Jungi and McGregor, unpublished data) indicate that labeled lymphoblasts from the thoracic duct lymph of Listeria-infected CONV donors can move in substantial numbers from the blood into Listeria-induced exudates borne by GF rats.…”
Section: Discussionsupporting
confidence: 74%
“…been implicated in the expression of DTH (11), and since DTH reactions are impaired in GF subjects (14,15,32,33), it was of interest to compare the generation of MCA in GF and CONV subjects. To this end, six GF Fischer and a group of CONV Lewis x DA F1 hybrid rats were immunized in the forepaws with living L. monocytogenes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lymphoid organs in these animals are consid-erably smaller and contain very few mature lymphocytes (11, 151, 209). Lev and Battisto (122) have reported that germfree guinea pigs have impaired delayed-type hypersensitivity responses, and this has been confirmed by others (212,214). Jungi and McGregor (94) reported that macrophages in gnotobiotic rats had an impaired capacity for chemotaxis, but neutrophil chemotaxis, serum levels of chemotactic activity, and the capacity of lymphocytes to generate macrophage chemotactic factor were all normal.…”
Section: Hormonal Factorsmentioning
confidence: 68%